Topical Application of the PI3Kβ-Selective Small Molecule Inhibitor TGX-221 Is an Effective Treatment Option for Experimental Epidermolysis Bullosa Acquisita - Zillikens, Hannah; Kasprick, Anika; Osterloh, Colin; Gross, Natalie; Radziewitz, Michael; Hass, Cindy; Hartmann, Veronika; Behnen-Härer, Martina; Ernst, Nancy; Boch, Katharina; Vidarsson, Gestur; Visser, Remco; et al. (Frontiers in Medicine, 2021)
Class I phosphoinositide 3-kinases (PI3K) have been implemented in pathogenesis of experimental epidermolysis bullosa acquisita (EBA), an autoimmune skin disease caused by type VII collagen (COL7) autoantibodies. Mechanistically, inhibition of specific PI3K isoforms, namely PI3Kbeta or PI3Kdelta, impaired immune complex (IC)-induced neutrophil activation, a key prerequisite for EBA pathogenesis. Data unrelated to EBA showed that neutrophil activation is also modulated by PI3Kalpha and gamma, but their impact on the EBA has, so far, remained elusive. To address this and to identify potential therapeutic targets, we evaluated the impact of a panel of PI3K isoform-selective inhibitors (PI3Ki) on neutrophil function in vitro, and in pre-clinical EBA mouse models. We document that distinctive, and EBA pathogenesis-related activation-induced neutrophil in vitro functions depend on distinctive PI3K isoforms. When mice were treated with the different PI3Ki, selective blockade of PI3Kalpha (alpelisib), PI3Kgamma (AS-604850), or PI3Kbeta (TGX-221) impaired clinical disease manifestation. When applied topically, only TGX-221 impaired induction of experimental EBA. Ultimately, multiplex kinase activity profiling in the presence of disease-modifying PI3Ki identified unique signatures of different PI3K isoform-selective inhibitors on the kinome of IC-activated human neutrophils. Collectively, we here identify topical PI3K inhibition as a potential therapeutic target for the treatment of EBA.